Tubal patency assessment using sequential transvaginal ultrasound and hysterosalpingo-foam sonography after methotrexate treatment for tubal pregnancy. Issue 2 (February 2022) - Melcer, Yaakov; Gat, Itai; Dvash, Shira; Copel, Laurian; Pekar-Zlotin, Marina; Youngster, Michal; Maymon, Ron
Abstract: Research question: What is the efficacy of sequential two-dimensional transvaginal ultrasound (2D-US) and hysterosalpingo-foam sonography (HyFoSy) after methotrexate (MTX) treatment for tubal pregnancy among patients who desire a future pregnancy? Design: A prospective trial conducted between May 2019 and November 2020. Patients who had a suspected tubal ectopic pregnancy diagnosed by ultrasound and treated by MTX were included. These patients underwent sequential transvaginal 2D-US assessment of the pelvic organs and a complementary HyFoSy for tubal patency. The primary outcome was tubal obstruction in the affected side. Results: A total of 360 women underwent sequential transvaginal 2D-US assessment of the pelvic organs and a complementary HyFoSy for tubal patency. Of these, 40 (11.1%) women fulfilling the inclusion criteria were enrolled. In six out of 40 (15%), hydrosalpinx of the affected tube was found during the initial transvaginal ultrasound examination and were excluded from further investigation. In the remaining 34 (85%) patients, HyFoSy was carried out. Tubal block was found in 10 out of 34 (29.4%) patients. Of these, eight out of 34 (23.5%) and two out of 34 (5.9%) had a proximal block of the affected tube and bilateral proximal obstruction, respectively. Hysterosalpingography confirmed the tubal obstruction in all the affected cases. No procedure-related complications were documented. Conclusions: Forty per cent of women who were treated by MTX for tubal pregnancy were diagnosed with tubal obstruction. We recommend that sequential transvaginal ultrasound and HyFoSy become part of routine follow-up for these women, thus offering them timely referral to the appropriate specialist.